Development of a floating multiple unit controlled-release system for mosapride - Kumaran, K Senthil; Manjunath, S Y; Wamorkar, Vinay V (Asian Journal of Pharmaceutics (AJP), 2014)
Floating beads are often used for controlled drug release as they have a gastroretentive property without affecting the gastric emptying rate. In the present study mosapride-controlled release beads were prepared with the help of the ionotropic gelation method, using sodium alginate containing KHCO3 as the gas-forming agent. The physical characterization of the mosapride beads was examined by SEM. The results showed that the shape and texture of the beads were uniform before and after dissolution.The percentage of mosapride drug entrapment efficiency ranged from 97.4 ï‚± 0.08 to 99.1 ï‚± 0.04.The percentage of mosapride content from the beads was determined by high-performance liquid chromatography (HPLC) and ranged from 97.9 ï‚± 0.08 to 99.6 ï‚± 0.01. The in-vitro percentage release of mosapride from the beads at the end of 14 hours ranged from 90.0 ï‚± 0.2 to 99.5 ï‚± 0.12. The formulated beads in formulations 1 and 3 were sealed in vials and kept for 90 days at 40Â°C / 75% RH. After 90 days of exposure the percentage drug content was found to be 99.2 ï‚± 0.04. The Floating beads designed for the gastroretentive dosage form could be suitable for controlled drug delivery.